European Union Copyright Protection for AI-Generated Works - Assinen, Senja (My University, 2018)
This thesis assesses the copyright protection of AI-generated works in the European Union. AI-generated work means a work of art that is generated independently by an AI system that relies on machine learning and artificial neural network technology in functioning. The human input in the creation process of an AI-generated work is non-existent. Today, the AI-generated works can be found in almost every copyrightable medium, such as in the field of music, art and literature. The aim of this thesis is two-fold. The aim of the first part of this thesis is to analyze whether the AI-generated works are currently protected under the European Union copyright law. In order to answer this question, the case law of the Court of Justice of the European Union in the field is analyzed. The aim of the second part of this thesis is to assess whether the AI-generated works should be protected and if the answer is yes, who should be allocated the rights and by which legal tool. The questions analyzed in this thesis are significant as the importance of AI-generated works in our society is constantly increasing. If the AI-generated works are not protected and the protection regime remain unclear, this will have a negative impact on investments. Consequently, the number of valuable works would decrease in the society. This thesis focuses on the European Union copyright law and follows the traditional legal dogmatic approach. In addition, de lege ferenda approach is adopted in the second part of this thesis. The conclusion of this thesis is that the AI-generated works are not currently protected under the European Union copyright law. This conclusion is mainly based on the finding that the AI-generated works are not regarded original work of authorship established by the case law of the Court of Justice of the European Union. It is further concluded that the current legislative environment, in which the valuable AI-generated works fall within the public domain should be avoided. It is proposed that the authorship in the AI-generated works would be allocated to the user of the AI-system. For this purpose, it is suggested that EU would adopt the US based work-for-hire doctrine, under which the AI system would be regarded as a creative “employee” of the user.
Keywords: Information society, copyright law, intellectual property law, EU law, artificial intelligence